INTEGRATED LESSONS AS A MEANS OF INCREASING THE INTEREST OF HIGHER EDUCATION STUDENTS IN THE STUDY OF MATHEMATICS - Dyadenchuk , Alena (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The paper provides a theoretical justification and analyzes the methodical-mathematical support for training students of higher education to study mathematics based on an integrative approach. It has been established that the specifics of the integrated teaching of mathematics is that the problem under consideration should be related to both mathematics and physics, and its study should be multifaceted, comprehensive, which does not allow to miss any of its components. The proposed approach helps to improve the quality of knowledge of the students of education, forms general concepts in both mathematics and physics, generalizing computational and measuring skills and abilities, helps in deeper understanding and assimilation of the program material of the mathematics course at the level of application of knowledge, abilities, and skills in new conditions.